Influence of Neutrophil Defects on Burkholderia cepacia Complex Pathogenesis - Porter, Laura A.; Goldberg, Joanna B. (Frontiers in Cellular and Infection Microbiology, 2011)
The Burkholderia cepacia complex (Bcc) is a group of Gram-negative bacteria that are ubiquitous in the environment and have emerged as opportunistic pathogens in immunocompromised patients. The primary patient populations infected with Bcc include individuals with cystic fibrosis (CF), as well as those with chronic granulomatous disease (CGD). While Bcc infection in CF is better characterized than in CGD, these two genetic diseases are not obviously similar and it is currently unknown if there is any commonality in host immune defects that is responsible for the susceptibility to Bcc. CF is caused by mutations in the CF transmembrane conductance regulator, resulting in manifestations in various organ systems, however the major cause of morbidity and mortality is currently due to bacterial respiratory infections. CGD, on the other hand, is a genetic disorder that is caused by defects in phagocyte NADPH oxidase. Because of the defect in CGD, phagocytes in these patients are unable to produce reactive oxygen species, which results in increased susceptibility to bacterial and fungal infections. Despite this significant defect in microbial clearance, the spectrum of pathogens frequently implicated in infections in CGD is relatively narrow and includes some bacterial species that are considered almost pathognomonic for this disorder. Very little is known about the cause of the specific susceptibility to Bcc over other potential pathogens more prevalent in the environment, and a better understanding of specific mechanisms required for bacterial virulence has become a high priority. This review will summarize both the current knowledge and future directions related to Bcc virulence in immunocompromised individuals with a focus on the roles of bacterial factors and neutrophil defects in pathogenesis.